The Use of Navigation or Robotic-Assisted Technology in Total Knee Arthroplasty Does Not Reduce Postoperative Pain - Zak, Stephen Gerard; Yeroushalmi, David; Tang, Alex; Meftah, Morteza; Schnaser, Erik; Schwarzkopf, Ran (The Journal of Knee Surgery, 2021)
The use of intraoperative technology (IT), such as computer-assisted navigation (CAN) and robot-assisted surgery (RA), in total knee arthroplasty (TKA) is increasingly popular due to its ability to enhance surgical precision and reduce radiographic outliers. There is disputing evidence as to whether IT leads to better clinical outcomes and reduced postoperative pain. The purpose of this study was to determine if use of CAN or RA in TKA improves pain outcomes. This is a retrospective review of a multicenter randomized control trial of 327 primary TKAs. Demographics, surgical time, IT use (CAN/RA), length of stay (LOS), and opioid consumption (in morphine milligram equivalents) were collected. Analysis was done by comparing IT (n = 110) to a conventional TKA cohort (n = 217). When accounting for demographic differences and the use of a tourniquet, the IT cohort had shorter surgical time (88.77 ± 18.57 vs. 98.12 ± 22.53 minutes; p = 0.005). While postoperative day 1 pain scores were similar (p = 0.316), the IT cohort has less opioid consumption at 2 weeks (p = 0.006) and 1 month (p = 0.005) postoperatively, but not at 3 months (p = 0.058). When comparing different types of IT, CAN, and RA, we found that they had similar surgical times (p = 0.610) and pain scores (p = 0.813). Both cohorts had similar opioid consumption at 2 weeks (p = 0.092), 1 month (p = 0.058), and 3 months (p = 0.064) postoperatively. The use of IT in TKA does not yield a clinically significant reduction in pain outcomes. There was also no difference in pain or perioperative outcomes between CAN and RA technology used in TKA.
Keywords: navigation; robotic-assisted; total knee arthroplasty; opioid; pain